Cytokine‐mediated modulation of the hepatic miRNome: miR‐146b‐5p is an IL‐6‐inducible miRNA with multiple targets. Issue 5 (26th August 2018) - Kirchmeyer, Mélanie; Servais, Florence A.; Hamdorf, Matthias; Nazarov, Petr V.; Ginolhac, Aurélien; Halder, Rashi; Vallar, Laurent; Glanemann, Matthias; Rubie, Claudia; Lammert, Frank; Kreis, Stephanie; Behrmann, Iris
Abstract: Interleukin‐6 (IL‐6)‐type cytokines play important roles in liver (patho‐)biology. For instance, they regulate the acute phase response to inflammatory signals and are involved in hepatocarcinogenesis. Much is known about the regulation of protein‐coding genes by cytokines whereas their effects on the miRNome is less well understood. We performed a microarray screen to identify microRNAs (miRNAs) in human hepatocytes which are modulated by IL‐6‐type cytokines. Using samples of 2 donors, 27 and 68 miRNAs (out of 1, 733) were found to be differentially expressed upon stimulation with hyper‐IL‐6 (HIL‐6) for up to 72 h, with an overlap of 15 commonly regulated miRNAs. qPCR validation revealed that miR‐146b‐5p was also consistently up‐regulated in hepatocytes derived from 2 other donors. Interestingly, miR‐146b‐5p (but not miR‐146a‐5p) was induced by IL‐6‐type cytokines (HIL‐6 and OSM) in non‐transformed liver‐derived PH5CH8 and THLE2 cells and in Huh‐7 hepatoma cells, but not in HepG2 or Hep3B hepatoma cells. We did not find evidence for a differential regulation of miR‐146b‐5p expression by promoter methylation, also when analyzing the TCGA data set on liver cancer samples. Inducible overexpression of miR‐146b‐5p in PH5CH8 cells followed by RNA‐Seq analysis revealed effects on multiple mRNAs, including those encoding IRAK1 and TRAF6 crucial for Toll‐like receptor signaling. Indeed, LPS‐mediated signaling was attenuated upon overexpression of miR‐146b‐5p, suggesting a regulatory loop to modulate inflammatory signaling in hepatocytes. Further validation experiments suggest DNAJC6, MAGEE1, MPHOSPH6, PPP2R1B, SLC10A3, SNRNP27, and TIMM17B to be novel targets for miR‐146b‐5p (and miR‐146a‐5p). Abstract : IL‐6‐type cytokines up‐regulate miR‐146b‐5p expression in liver cells, an anti‐inflammatory miRNA with multiple targets shared with miR‐146a‐5p.